Investigation of salt intrusion in the Kuantan Estuary during high tide condition adopting 1-D analytical solution - Wong, Jia Eng (2017)
Faculty of Civil Engineering and Earth Resources Dissertations Summary After the construction of the Kobat Barrage in the 1970’s, the water intake station in the Kuantan Estuary had been free from salt intrusion problem. But until recently, the water intake station at Kg.Kobat was reported being affected saline water due to the El-Nino phenomenon. Hence, it is important to reassess the saline intrusion condition in the Kuantan estuary. The objectives of this research are: 1) to investigate the salinity distribution in the Kuantan Estuary during the dry season at high tide; 2) to test 1-D analytical salt intrusion model in the Kuantan Estuary and 3) to calibrate and validate the 1-D analytical salt intrusion model in the Kuantan Estuary. In this study, the salinities along the estuary were measured and recorded by using moving boat technique. A one-dimensional analytical salt intrusion model has been successfully applied to the Kuantan Estuary during spring tide with the high water slack condition. The computed and calibrated results of Van der Bugh’s coefficient K, dispersion D0 and the tidal extrusion E obtained from the study have values of 0.50, 15.06/m and 5600m, respectively. The Van der Burgh’s coefficient and tidal excursion were validated by comparing the simulated outcome from the two surveys. The RMSE and NSE average values of about 3.7ppt and 85% are considered acceptable. In overall, the results of this study have provided an insight into the current salinity condition in the Kuantan Estuary after the construction of the barrage in the late 1970’s.